WEBGIS PERBANDINGAN DAN PENYEBARAN RUMAH SAKIT, PUSKESMAS, TENAGA KESEHATAN (AHLI GIZI) TERHADAP KUALITAS KESEHATAN DI KABUPATEN KUDUS TAHUN 2021-2022 - Tedy Firmansyah; Bambang Agus Herlambang, Ahmad Khoirul Anam (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Health is a crucial aspect in the development of a region. The quality of health services can determine people's welfare. This research aims to map the distribution of hospitals, health centers and nutritionist health workers in Kudus Regency, Central Java, throughout 2021-2022. This research uses the waterfall method using Quantum GIS software. The variables that are the focus of the research cover nine sub-districts in Kudus Regency, Central Java, in the 2021-2022 period with data sourced from the Central Statistics Agency. It is hoped that the research results can identify areas that require improvements in health facilities and the distribution of health workers so that they can make a positive contribution to local community health services.